Application of Synthesized Tetragonal Structured Zirconium Oxide Nanoparticles in the Photodegradation of Victoria Blue B and Acridine Orange Dye - K. Yogendra (New Insights into Physical Science Vol. 12, 2021)
The unique properties of nanoparticles have attracted attention because of their scientific and industrial importance. Various metal oxide nanoparticles have been used to eliminate the organic pollutants. ZrO is an eco-friendly material, non-toxic, cost effective and has high thermal and chemical stability. ZrO nanoparticles were prepared and characterized by XRD, SEM-EDAX, TEM, BET and UV–visible spectroscopic studies. Zirconium oxide was synthesized from zirconium nitrate and urea by solution combustion method. Nano-photocatalyst zirconium oxide was investigated by XRD, SEM-EDAX, TEM, UV absorbance spectroscopy and specific surface area analysis. The distribution size of ZrO was found to be less than 17nm and was confirmed by XRD and TEM studies. The ZrO nano-photocatalyst confirmed the tetragonal phase by XRD. EDAX revealed the formation of ZrO. The efficiency of ZrO nanoparticles in the photodegradation of victoria blue B and acridine orange dye under sunlight was investigated. The results revealed that the degradation efficiency was found to be 95.42% for VBB (at 0.030 g/pH 6/1×10-4mol/dm3) and 92.52% for AO (at 0.035 g/pH 4/1×10-4mol/dm3). Further, the degradation efficiency shown highest in VBB dye when compare to AO dye. The ZrO nanoparticles have been found to be suitable for the treatment of textile effluents.